2016
DOI: 10.1007/s00268-016-3660-5
|View full text |Cite
|
Sign up to set email alerts
|

The Yield of Fever, Inflammatory Markers and Ultrasound in the Diagnosis of Acute Cholecystitis: A Validation of the 2013 Tokyo Guidelines

Abstract: The 2013 Tokyo Guidelines were slightly better in predicting acute cholecystitis but over diagnosed two-thirds of normal gallbladders compared to neutrophil count alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…However, the latter study found that neutrophil count was the only independent predictor of acute cholecystitis for which a significant difference was evident on the basis of multivariate analysis . The use of neutrophil count alone for the definitive diagnosis of acute cholecystitis is unrealistic.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, the latter study found that neutrophil count was the only independent predictor of acute cholecystitis for which a significant difference was evident on the basis of multivariate analysis . The use of neutrophil count alone for the definitive diagnosis of acute cholecystitis is unrealistic.…”
Section: Introductionmentioning
confidence: 94%
“…To date, no diagnostic criteria for acute cholecystitis meriting that title have been established other than TG13 . However, studies of the diagnostic yield of the TG13 diagnostic criteria are limited .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the patients are asymptomatic, and approximately 20% of symptomatic patients present with acute cholecystitis (AC). 1 …”
Section: Introductionmentioning
confidence: 99%